Identifying CRAAP on the Internet: A Source Evaluation Intervention - Muis, Krista Renee; Denton, Courtney; Dubé, Adam (Advances in Social Sciences Research Journal, 2022)
Individuals of all ages struggle to determine the reliability of information on the internet. To address this common issue, many educational institutions have endorsed the CRAAP test (i.e., currency, relevance, authority, accuracy, and purpose) as an effective approach to support identification of unreliable information. The present study extended the CRAAP test by incorporating a modeling component on how to evaluate and integrate multiple sources of varying quality on the internet and evaluated the efficacy of this source evaluation training intervention. Eighty-two participants across Canada were recruited to evaluate six authentic webpages and then construct an argument on a specific topic. Half the sample received training to examine the currency, relevance, authority, accuracy, and purpose (i.e., CRAAP) of the webpages before completing the online activity. Results revealed that the intervention group provided more accurate rank-ordering of the webpages, but no differences were found between groups on source integration via an argumentative essay. These findings suggest that the CRAAP test is effective in improving individuals’ evaluations of online sources but is not effective in promoting better quality source integration.